Physical functioning in patients with chronic kidney disease stage G3b‐5 in Japan: The reach‐J CKD cohort study. Issue 12 (17th August 2021) - Okubo, Reiko; Kondo, Masahide; Tsunoda, Ryoya; Nagai, Kei; Kai, Hirayasu; Saito, Chie; Hoshino, Junichi; Okada, Hirokazu; Narita, Ichiei; Wada, Takashi; Kashihara, Naoki; Robinson, Bruce; et al.
Abstract: Aim: Chronic kidney disease (CKD) is an important public health problem. Recently, CKD has been found to be associated with poor physical functioning in community‐dwelling elderly individuals. However, the physical functioning of non‐dialysis (ND) patients with advanced CKD treated by nephrologists is unknown. Methods: Patients with ND‐CKD stage G3b‐5 who participated in a nationwide Reach‐J CKD cohort study were included in this study. Physical functioning and physical activity were assessed by the Katz Index, Lawton‐Body instrumental activities of daily living (IADL) scale, and Rapid Assessment of Physical Activity questionnaire of the international CKD Outcomes and Practice Patterns Study (CKDopps) questionnaires. Dichotomies between good and poor physical functioning and physical activity scores were explored. Results: Among 1628 patients, 84.3% had good physical functioning. Poor physical functioning was more common with older age ( p  < .001), higher CKD stage ( p  < .05), and comorbid conditions such as diabetes ( p  < .001), cardiovascular disease ( p  < .05), cerebrovascular disease ( p  < .001), and cancer (non‐skin) ( p  < .05). Forty percent of the patients were inactive. Physical inactivity was more common with older age ( p  < .001) and higher CKD stage ( p  < .001). Conclusion: A minority, but sizeable proportion of patients with advanced CKD treated by nephrologists in Japan have some disability in ADLs/IADLs. Nephrologists need to routinely assess the physical functioning and physical activity of patients with advanced CKD to provide individualized guidance and comprehensive support to these patients for their daily life. SUMMARY AT A GLANCE: Among non‐dialysis stage G3b‐5 subjects, poor physical functioning was more common with older age, higher CKD stage, and comorbid conditions such as diabetes, cardiovascular disease, cerebrovascular disease, and cancer (non‐skin). The study stressed the need for nephrologists to routinely assess the physical functioning and physical activity of patients with advanced CKD to provide individualized guidance and comprehensive support for their daily life.